Development Of E-Commerce Transactions And Its Influence On Labor Absorption - Rahmat Pujiyanto; Cicih Ratnasih (Edunity Kajian Ilmu Sosial dan Pendidikan, 2024)
Global online retail is experiencing rapid growth, as reflected in the value of e-commerce, which is estimated to have grown by over 230 percent to $4.48 trillion, or Rp60.467 trillion, in 2021, from just $1.8 trillion in 2014. Online shopping has now become a popular pastime worldwide, particularly among young people. In addition to exciting new experiences, the prices of purchased items are also cheaper compared to traditional shopping. This sort of research is qualitative, utilizing secondary data obtained through literature reviews and statistical data. The research findings indicate that the value of e-commerce grew by over 230 percent to $4.48 trillion, or Rp60.467 trillion, in 2021, from just $1.8 trillion in 2014. In 2020 alone, the total turnover of the Asian continent reached $1.7 trillion USD. Moreover, this growth is projected to continue increasing in 2025, with an expected 51% increase to $2.5 trillion. China had sales of $1.3 trillion and is projected to grow to nearly $2 trillion by 2025. These figures exceed sales in Europe and North America. In 2020, the turnover of the European continent was $460 billion and North America was $588 billion. These values are significantly lower compared to China's sales. E-commerce in Indonesia also experienced strong growth since the beginning of 2020 due to the pandemic. The trading business grew by around 33% in 2020, and its main value increased rapidly from Rp 253 billion to Rp 337 billion. The role of business law in e-commerce transactions applies similarly to other purchasing and trading activities. With regulations in place regarding this matter, legal certainty is provided for the conduct of electronic transactions in Indonesia and internationally.